Overexpression of cysteine‐glutamate transporter and CD44 for prediction of recurrence and survival in patients with oral cavity squamous cell carcinoma. Issue 11 (10th October 2018) - Lee, Jae Ryung; Roh, Jong‐Lyel; Lee, Sun Mi; Park, Yangsoon; Cho, Kyung‐Ja; Choi, Seung‐Ho; Nam, Soon Yuhl; Kim, Sang Yoon
Abstract: Background: This study analyzed the expression of CD44 and cystine‐glutamate transporter SLC7A11 (xCT) in primary oral cavity squamous cell carcinoma (SCC) and the relationships of expression to tumor recurrence and patient survival. Methods: Associations between CD44 and xCT expression and clinicopathologic results were analyzed in 231 patients with oral cavity SCC. Cox proportional hazard analyses were used to identify factors associated with recurrence‐free survival (RFS), disease‐specific survival (DSS), and overall survival (OS). Results: Overexpression of CD44 and/or xCT was associated with advanced T classification, perineural invasion, and lymphovascular invasion ( P < .05 each). High expression of xCT was also associated with nodal metastasis and depth of invasion ( P < .01 each). Multivariate analysis indicated that high expression of xCT and both xCT and CD44 were independent predictors of poor RFS, DSS, and OS ( P < .05 each). Conclusion: Overexpression of xCT or xCT plus CD44 may predict posttreatment recurrence and survival in patients with oral cavity SCC.